Syberyjska dziatwa : wojenne losy kresowiakow - Budzynska, Julia Hubert (Lublin : Norbertinum, 1993)
The story of one person deported to Russsia and her final return to Poland after WW II.
Keywords: Budzynska, Julia Hubert; World War, 1939-1945 -- Deportations from Poland; Polish people -- Soviet Union -- Biography; World War, 1939-1945 -- Personal narratives, Polish; Population transfers -- Poles